2020
DOI: 10.1088/1361-6641/abadba
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Se/(S+Se) compositional ratios on the performance of SnS-based solar cell: a numerical simulation

Abstract: In this work, a path to overcome the highest current efficiency on SnS thin-film solar cells by the Se incorporation is presented. We carried out a theoretical study of the effect of different Se/(S + Se) compositional ratios (CRs) (from 0.0 to 1.0) on the solar cell performance. In this sense, an improvement on power conversion efficiency (PCE) by decreasing the energy band gap (theoretical Se incorporation) from 1.35 to 1.08 eV was observed. All electrical output parameters (open-circuit voltage, short-circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…[ 25 ] Gong et al demonstrated that the linear change in E g with a decrease in the sulfur content varies from 1.29 to 1.05 eV for SnS 1− x Se x material. [ 26 ] The bandgap [ 26 ] and electron affinity [ 27 ] of SnS 1− x Se x at different sulfur mole fraction can be calculated as follows:Eg(SnS1xSex)=false(1xfalse)Eg(SnS)+(x)Eg(SnSe)bx(1x)$$E_{\text{g}} \left(\right. \left(\text{SnS}\right)_{1 - x} \left(\text{Se}\right)_{x} \left.\right) = \left(\right.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] Gong et al demonstrated that the linear change in E g with a decrease in the sulfur content varies from 1.29 to 1.05 eV for SnS 1− x Se x material. [ 26 ] The bandgap [ 26 ] and electron affinity [ 27 ] of SnS 1− x Se x at different sulfur mole fraction can be calculated as follows:Eg(SnS1xSex)=false(1xfalse)Eg(SnS)+(x)Eg(SnSe)bx(1x)$$E_{\text{g}} \left(\right. \left(\text{SnS}\right)_{1 - x} \left(\text{Se}\right)_{x} \left.\right) = \left(\right.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…[25] Gong et al demonstrated that the linear change in E g with a decrease in the sulfur content varies from 1.29 to 1.05 eV for SnS 1Àx Se x material. [26] The bandgap [26] and electron affinity [27] of SnS 1Àx Se x at different sulfur mole fraction can be calculated as follows:…”
Section: Simulation Methodologymentioning
confidence: 99%
“…All simulations are run with a global illumination of AM 1.5 spectra. The SCAPS‐1D program is used to resolve the Poisson equation as well as the continuity equations of both charge carriers 50‐52 …”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
“…The SCAPS-1D program is used to resolve the Poisson equation as well as the continuity equations of both charge carriers. [50][51][52] The electric field E of p-n junction is related to the space charge density ρ:…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
“…In 2014, H Ullah et al proposed a solar cell model based on SnS and got an efficiency of 15% with the model SnS/CdS/ ZnO at an acceptor concentration of 10 19 cm −3 [35]. In 2020, M D L Santos et al performed numerical simulation of SnS based thin-film solar cell where compositional ratios of Se/(S + Se) was used between 0.0 to 1.0 and found a maximum PCE of 11.78% at a compositional ratio of 0.75 with 800 nm thickness [36]. In 2020, S Ahmmed et al proposed planar heterostructure of SnS-based solar cells using CeO X ETL and reported a maximum PCE of 25.1% [24].…”
Section: Introductionmentioning
confidence: 99%